(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The aim of this research is to investigate the means and methods that contributed to the coining of the informational term related to data, information, and knowledge. The qualitative approach based on printed sources and extensive reading of non-printed sources and documents, as well as audio-visual materials such as recorded seminars, has been adopted in this research. The outcomes of the research have proved that there is a short come in the coining of the informational terms in the Arabic language, and resort to translation or Arabicization or transliteration because of the hegemony of foreign languages ​​that was more obvious among Arab specialists. Moreover, the outcomes of the research have shown the existence of various problems and obstacles encountered in the coining and usage of the informational term. Hence, more studies on this issue are widely required.